Atrial Fibrillation : Improving Therapy via Engineering Advancements - Rust, Michael J. (McGraw-Hill's AccessEngineering., 2020)
This case will explore atrial fibrillation from several perspectives, including the underlying physiology, clinical relevance, and instrumentation used for diagnosis and therapy. Students will identify and investigate unmet clinical needs that led to recent developments in technologies to treat atrial fibrillation.